Dermoscopic Features of Facial Pigmented Skin Lesions. (31st January 2013) - Goncharova, Yana; Attia, Enas A. S.; Souid, Khawla; Vasilenko, Inna V.
Abstract : Four types of facial pigmented skin lesions (FPSLs) constitute diagnostic challenge to dermatologists; early seborrheic keratosis (SK), pigmented actinic keratosis (AK), lentigo maligna (LM), and solar lentigo (SL). A retrospective analysis of dermoscopic images of histopathologically diagnosed clinically-challenging 64 flat FPSLs was conducted to establish the dermoscopic findings corresponding to each of SK, pigmented AK, LM, and SL. Four main dermoscopic features were evaluated: sharp demarcation, pigment pattern, follicular/epidermal pattern, and vascular pattern. In SK, the most specific dermoscopic features are follicular/epidermal pattern (cerebriform pattern; 100% of lesions, milia-like cysts; 50%, and comedo-like openings; 37.50%), and sharp demarcation (54.17%). AK and LM showed a composite characteristic pattern named "strawberry pattern" in 41.18% and 25% of lesions respectively, characterized by a background erythema and red pseudo-network, associated with prominent follicular openings surrounded by a white halo. However, in LM "strawberry pattern" is widely covered by psewdonetwork (87.5%), homogenous structureless pigmentation (75%) and other vascular patterns. In SL, structureless homogenous pigmentation was recognized in all lesions (100%). From the above mentioned data, we developed an algorithm to guide in dermoscopic features of FPSLs.